2012
DOI: 10.1088/0004-637x/762/2/77
|View full text |Cite
|
Sign up to set email alerts
|

Superdense Galaxies and the Mass-Size Relation at Low Redshift

Abstract: We search for massive and compact galaxies (superdense galaxies, hereafter SDGs) at z = 0.03 − 0.11 in the Padova-Millennium Galaxy and Group Catalogue, a spectroscopically complete sample representative of the local Universe general field population. We find that compact galaxies with radii and mass densities comparable to high-z massive and passive galaxies represent 4.4% of all galaxies with stellar masses above 3 × 10 10 M ⊙ , yielding a number density of 4.3 × 10 −4 h 3 Mpc −3 . Most of them are S0s (70%)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
230
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(254 citation statements)
references
References 100 publications
(119 reference statements)
20
230
4
Order By: Relevance
“…1, these findings seem to trouble the current hierarchical paradigm of galaxy formation, where some relic systems at z ∼ 0 are actually expected to be found. In contrast, Poggianti et al (2013a) have found 4 galaxies fulfilling our same criteria (corresponding to 1.4% of their sample galaxies with masses larger than 8 × 10 10 M⊙), and all of these galaxies are old, with massweighted ages older than 8 Gyr. These numbers translate into a very large abundance of ∼ 10 −5 Mpc −3 .…”
Section: Abundance Vs Redshiftmentioning
confidence: 76%
See 3 more Smart Citations
“…1, these findings seem to trouble the current hierarchical paradigm of galaxy formation, where some relic systems at z ∼ 0 are actually expected to be found. In contrast, Poggianti et al (2013a) have found 4 galaxies fulfilling our same criteria (corresponding to 1.4% of their sample galaxies with masses larger than 8 × 10 10 M⊙), and all of these galaxies are old, with massweighted ages older than 8 Gyr. These numbers translate into a very large abundance of ∼ 10 −5 Mpc −3 .…”
Section: Abundance Vs Redshiftmentioning
confidence: 76%
“…Although observational studies at intermediate-and high-z do not point to a clear picture of how environment affects galaxy sizes (see Damjanov et al 2015b and references therein), recent cosmological simulations predict a larger fraction of massive compact systems in high-than in low-density regions (Stringer et al 2015). This prediction is supported by the fact that NGC 1277 -the only well-characterized compact, massive, ETG at z ∼ 0 -resides in the core region of a nearby rich cluster of galaxies (Trujillo et al 2014; see also Valentinuzzi et al 2010;Poggianti et al 2013a). Thus, the absence of compact galaxies at z < 0.2 could be related to the smaller fraction of dense structures in the area currently mapped by KiDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of the median size (i.e., the half-light radius r 1/2 ) of the population of massive (M Galaxy > 10 10 M ) quenched early-type galaxies (Q-ETGs) at given stellar mass has been widely highlighted in recent years (e.g., Daddi et al 2005;Trujillo et al 2007;McGrath et al 2008;van Dokkum et al 2008;Cassata et al 2011;Szomoru et al 2011;Barro et al 2013;Dullo & Graham 2013;Newman et al 2012;Poggianti et al 2013;Shankar et al 2013, just to cite a few). The size of the effect is quite large, with a decrease in median r 1/2 with increasing redshift ∝ (1 + z) −1 ; in coarse terms, this implies that, at a given stellar mass, the median half-light radius of Q-ETGs is about a factor of ∼2-3 smaller at z ∼ 2 than locally, corresponding to an increase of over an order of magnitude in the median mean stellar density within the half-light radius of galaxies.…”
Section: Introductionmentioning
confidence: 99%